THE ROLE OF AUDIO, VIDEO AND COMPUTER-MEDIATED COMMUNICATION IN LANGUAGE LEARNING - Xoliqulova Hulkaroy; Samadova Visola (TADQIQOTLAR, 2026)
Annotation. This article examines the role of audio, video, and computer- mediated communication (CMC) in language learning. It explains how these tools help learners develop listening, speaking, reading, and writing skills. The article also highlights the advantages and disadvantages of each method and emphasizes the importance of using them together. Special attention is given to modern digital technologies and communication platforms. The study concludes that the integration of audio, video, and CMC tools leads to more effective and interactive language learning.